PENGARUH FRAME RATE DATE BIT RATE TERHADAP KUALITAS LAYANAN STREAMING VIDEO MOBILE DEVICE COMMUNICATION WLAN 802.11n - Satrio Dimas Bagaskara; Sigit Kusmaryanto; Rusmi Ambarwati (Jurnal Mahasiswa TEUB, 2017)
Abstract — This study discusses the influence of Frame Rate and Bit Rate Video Streaming service to the quality of Mobile Device Communication WLAN 802 .11n. Video streaming service on mobile device communication with good quality highly expected by the penikmati service, the good quality of the video is influenced by a variety of factors, one of which Frame rate and Bit rate. Good video, not off of Quality of Service when shipping data (streaming video). This research was conducted by calculating 3 parameters of Quality of Service (QoS) that is delay, throughput, and pakcet loss. With the variation of the input frame rate 10fps, 30 fps, 512 Kbps bitrate and 50fps, 1024kbps, 2048kbps, data retrieval is done by the method of unicast and multicast with displacement distance as far as 250 meters from the acces point (standard WLAN 802.11 outdoor coverage area). The test results of each Quality of Service parameters the farthest distance is 150 metres, and the data obtained is better than unicast multicast method. The results of the data in accordance with standard ITU-T G. 114 to delay (delay of end to end < 150 s) on any variation of frame rate and video bit rate and the probability of packet loss (10%) packet loss > to video with a frame rate of 30, 50 and bit rate 1024, 2048 Kbps, quality service is bad enough based on ITU-T G. 1010, While for the variations of frame rate and bit rate 512 Kbps packet-loss value (5%) packet loss < service quality then runs good on coverage area acces point. The results of the data throughput of the greater the input frame rate and bit rate then the greater the throughput value anyway. The use of multicast or unicast method on the results of data retrieval is not much different, and mobility client is very influential towards the good and the bad quality of streaming video network. Keywords – Frame rate, Bit rate, WLAN 802 .11n, Mobile device communication, Quality of Service (QoS), Unicast, Multicast.Abstrak — Penelitian ini membahas tentang Pengaruh Frame Rate dan Bit Rate terhadap Kualitas Layanan Streaming Video Mobile Device Communication WLAN 802.11n. Layanan video streaming pada mobile device communication dengan kualitas baik sangat diharapkan oleh penikmati layanan ini, kualitas video yang baik dipengaruhi oleh berbagai faktor salah satunya Frame rate dan Bit rate. Video yang baik, tidak lepas dari Quality of Service saat pengiriman data (video streaming). Penelitian ini dilakukan dengan menghitung 3 parameter Quality of Service (QoS) yaitu delay, throughput, dan pakcet loss. Dengan variasi masukan frame rate 10fps, 30 fps, 50fps dan bitrate 512kbps, 1024kbps, 2048kbps, pengambilan data dilakukan dengan metode unicast dan multicast dengan perpindahan jarak sejauh 250 meter dari acces point (standart outdoor coverage area WLAN 802.11). Hasil pengujian dari setiap parameter Quality of Service jarak terjauh adalah 150 meter, dan data yang didapatkan lebih baik metode unicast dibandingkan multicast. Hasil data sesuai dengan standar ITU-T G.114 untuk delay (delay end to end < 150 s) pada setiap variasi frame rate dan bit rate video. Dan probabilitas packet loss (packet loss >10%) untuk video dengan frame rate 30, 50 dan bit rate 1024, 2048 Kbps, kualitas layanan cukup buruk berdasarkan ITU-T G.1010, Sementara untuk variasi frame rate 10 dan bit rate 512 Kbps nilai packet loss (packet loss <5%) maka kualitas layanan berjalan baik pada coverage area acces point. Hasil data throughput semakin besar masukan frame rate dan bit rate maka semakin besar pula nilai throughput. Penggunaan metode unicast maupun multicast pada hasil pengambilan data tidak jauh berbeda, dan mobilitas client sangat berpengaruh terhadap baik dan buruknya kualitas jaringan video streaming. Kata Kunci – Frame rate, Bit rate, WLAN 802.11n, Mobile device communication, Quality of Service (QoS), Unicast, Multicast .